Pengaruh Profitabilitas, Kebijakan Hutang, dan Kebijakan Deviden Terhadap Nilai Perusahaan Sektor Teknologi Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Alda Rizqi Alfiyaturrahmah; Cahyani Nuswandari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research examines how financial performance and corporate financial policies contribute to company value of technology firms listed on the Indonesia Stock Exchange during 2021-2023. This analysis focuses on profitability, leverage strategy, and payout approach as key factors influencing market valuation. Data sourced from yearly financial reports were examined through quantitative methods. A total of 69 companies were selected through a selective sampling process based on data availability and fiscal performance criteria. The observational study employs multiple linear regression to evaluate the connection between the variables. The findings indicate that higher profitability is associated with an increase in firm value, while greater reliance on debt tends to reduce market valuation. In contrast, payout approach demonstrates a favorable association with firm value, suggesting that dividend distribution is perceived as a positive signal by investors, Overallm the outcomes emphasize the relevance of financial decision-making in shaping investor perceptions and enterprise value within the technology sector.